Kravtsov А.G. Development of a mathematical model for the interaction of electrically active het-erogeneous fine-dispersed systems at the interface between the friction surface and the lubricating me-dium - Кравцов, А.Г. (Problems of Tribology, 2017)
Theoretical studies of the formation of an oil film on a friction surface in the presence of solutions of fullerenes in a lubricant are performed in the article. The mathematical model is developed on the basis of the interaction of electrically active heterogeneous fine-dispersed systems on the interface between the friction surface and the lubricating medium and is described by the differential Poisson equation. The relationship between the electrostatic field of the friction surface and the electric field in the bulk of the liquid is shown. It has been theoretically established that the use of "solvents" of fullerenes, which may be highly oleic vegetable oils, can be "confused" with the process of micelle formation, where the core of the micelle is a fullerene molecule surrounded by molecules, for example, oleic or stearic acid. It is shown that under the action of the stress-strain state of surface layers, the friction surface acts as an "electrostatic force field generator", which influences the formation of an electric field in the volume of the oil film. Expressions are obtained for calculating the strength of the total electric field of the "friction surface + lubricant" system. Keywords: electrostatic field strength, clustering, micellization, fullerenes, tribosystems, lubricating me